2009
DOI: 10.1164/rccm.200903-0322oc
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Epithelial-derived Fibroblasts to Bleomycin-induced Lung Fibrosis

Abstract: Rationale: Lung fibroblasts are key mediators of fibrosis resulting in accumulation of excessive interstitial collagen and extracellular matrix, but their origins are not well defined. Objectives: We aimed to elucidate the contribution of lung epithelium-derived fibroblasts via epithelial-mesenchymal transition (EMT) in the intratracheal bleomycin model. Methods: Primary type II alveolar epithelial cells were cultured from Immortomice and exposed to transforming growth factor-b 1 and epidermal growth factor. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
357
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 367 publications
(393 citation statements)
references
References 45 publications
20
357
2
3
Order By: Relevance
“…9,10,25,29,32,84e88 In two independent experiments, a substantial population of myofibroblasts reported transgenic expression from an incomplete section of the human surfactant protein C promoter after lung injury. 32,86 Because transcription of endogenous surfactant protein C is specific for type II airway epithelial cells, these results support the epithelial-tomesenchymal transition hypothesis that pathogenic myofibroblasts originate from dedifferentiated epithelial cells. 79 However, a different reporter system inserted into the endogenous mouse Sftpc locus found epithelial cells did not become myofibroblasts in the bleomycin lung injury model.…”
Section: Myofibroblasts In Lung Fibrosis and Degenerationsupporting
confidence: 58%
“…9,10,25,29,32,84e88 In two independent experiments, a substantial population of myofibroblasts reported transgenic expression from an incomplete section of the human surfactant protein C promoter after lung injury. 32,86 Because transcription of endogenous surfactant protein C is specific for type II airway epithelial cells, these results support the epithelial-tomesenchymal transition hypothesis that pathogenic myofibroblasts originate from dedifferentiated epithelial cells. 79 However, a different reporter system inserted into the endogenous mouse Sftpc locus found epithelial cells did not become myofibroblasts in the bleomycin lung injury model.…”
Section: Myofibroblasts In Lung Fibrosis and Degenerationsupporting
confidence: 58%
“…3D). In previous studies, we have used S100A4 as a fibroblast marker in the lungs (14)(15)(16)(17). Therefore, we evaluated lung sections by IHC for S100A4 expression and noted greater numbers of S100A4-positive fibroblasts in L188Q SFTPC mice compared with WT controls after bleomycin treatment ( Additionally, we wanted to determine whether lung mechanics were different at 3 wk after bleomycin treatment in L188Q SFTPC mice.…”
Section: Resultsmentioning
confidence: 99%
“…in mice by intubation as previously described (17). Lungs were harvested for histology, frozen tissue, bronchoalveolar lavage, or cell isolation as previously described (14)(15)(16)(17). L188Q SFTPC mice and controls were maintained on normal water ad libitum until transgene activation was desired.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 The impaired gas exchange and lung fibrogenesis can occur in the first week of the fibroproliferative phase of ARDS, which is similar to that observed in the fibrogenesis model following bleomycin exposure. 5,29 A previous study of an acid-induced lung injury model in mice also showed the crucial role of mechanical ventilation in initiating lung fibrogenesis, which was associated with TGF-b1-induced EMT and lung fibroblast proliferation. 3 Recent studies using alveolar type II epithelial cells and rats have demonstrated that cyclic mechanical stretch can lead to disorganization and ECM remodeling of the lung by activating the Wnt/b-catenin pathway and inducing EMT.…”
Section: Discussionmentioning
confidence: 97%